Effects of Exposure to Bisphenol A during Pregnancy on the Pup Testis Function. (21st May 2019) - Yang, Qingtao; Sui, Xuxia; Cao, Junjun; Liu, Caixia; Zheng, Shukai; Bao, Mian; Huang, Yuanni; Wu, Kusheng
Abstract : Testosterone plays an important prenatal role in male testis development. Bisphenol A (BPA) exposure during pregnancy affects testosterone levels and germ cell apoptosis of male pups, but little information is available for the mechanism. The aim of the present study was to investigate the mechanism by which BPA alters testosterone levels and germ cell apoptosis. Pregnant female C57BL/6J mice, throughout gestation, had access to drinking water containing BPA at 5 and 50 μ g/mL. Male pups were euthanized on postnatal days (PNDs) 1, 14, and 35. Relative to control, BPA exposure at 5 and 50 μ g/ml decreased testosterone level, as measured by chemiluminescent immunoassay, on PND14. Real-time PCR indicated mRNA levels for steroidogenic acute regulatory protein (StAR), cholesterol side-chain cleavage enzyme (CYP11A1), and 3- β -hydroxysteroid dehydrogenase/ △ -5-4 isomerase (3 β -HSD) were significantly lower in the BPA pups compared to control. Additionally, BPA increased the percentage of TUNEL-positive seminiferous tubules, decreased the mRNA level of Bcl-2, and increased Bax expression, indicative of increased apoptosis. These results suggest that BPA exposure in utero decreases the testosterone concentration by decreasing steroidogenic enzymes (StAR, CYP11A1, and 3 β -HSD). Furthermore, BPA exposure increases the apoptosis of germ cells, which is associated with proapoptotic changes in the levels of Bcl-2 and Bax.